How compassionate use enabled Israel to deliver the Pfizer‐BioNTech COVID‐19 vaccination to vulnerable children aged 12–15 years before regulatory approval. (28th December 2021) - Stein, Michal; Grossman, Zachi; Brosh‐Nissimov, Tal; Gottesman, Bat‐Sheva; Shahar, Arnon; Wechsler, Efrat; Matz, Eran; Cohen, Orna; Alroy‐Preis, Sharon; Anis, Emilia
Abstract: Aim: This paper describes the emergency, compassionate use of the COVID‐19 vaccination for high‐risk adolescents aged 12–15 years prior to approval by the American Food and Drugs Administration in May 2021. The target audience had underlying health conditions associated with severe disease and multisystem inflammatory syndrome in children (MIS‐C) or severely immunosuppressed household members. Methods: An orderly approval system was established in Israel for adolescents aged 12–15 years, based on a professional position paper and compassionate treatment regulations. From 12 February 2021, eligible adolescents were referred to the Israeli Ministry of Health for permission to vaccinate, via four health maintenance organisations. Data were collected about adverse events after vaccinations and the incidence of any cases of COVID‐19. Results: By 15 March 2021, the vaccine had been approved for 607 adolescents: 333 had received one dose, and 92 had received two doses. The median age was 14.6 years, and the major indication was obesity. Only one child tested positive for the virus, 4 days after vaccination, and no adverse effects were recorded. Conclusion: The emergency use of COVID‐19 vaccination for 333 adolescents aged 12–15, 92 of them with 2 doses, based on a position paper and compassionate treatment regulations, did not result in any adverse effects. Since 27 July 2021, the same process was further applied in Israel among younger children, aged 5–11, preceding formal release of the clinical trial.